A new species of the soft scale insect genus Pulvinaria Targioni Tozzetti (Hemiptera: Coccomorpha: Coccidae) on Rhododendron spp. in Northern Europe - Kahrer, Andreas; Hodgson, Chris J. (Zootaxa, 2024)
A new species of Pulvinaria, P. rhododendri Kahrer & Hodgson sp. nov. (Hemiptera: Coccomorpha: Coccidae), found on Rhododendron spp. (Ericaceae) in Denmark and Norway, is described and illustrated. Taxonomically, it appears to be close to P. camelicola Signoret and P. floccifera (Westwood). The geographic area of origin is uncertain but it has probably been introduced into northern Europe on imported live plant material. We also record P. camelicola from Norway for the first time, on Rhododendron sp.